Hosni Mubarak and the Future of Democracy in Egypt - Arafat, Dr. Alaa Al-Din Al-Din (Palgrave Macmillan, 2011)
As Mubarak's regimenearing its end becomes a strong possibility, many pressures, both foreign and domestic, are coming to bear on Egypt to bring democratic reforms to this struggling country. In The Mubarak Leadership and Future of Democracy in Egypt , Alaa Al-Din Arafat studies this new era and the obstacles that must be overcome.